Performance enhancement of selected vegetable oil as base fluid for drilling HPHT formation - Sulaimon, A.A. (Elsevier B.V., 2017)
Mineral oils are the base fluids of choice commonly used for the formulation of synthetic based mud (SBM) in drilling HPHT wells. However, the major drawbacks are largely related to environmental impact. They are highly toxic, non- biodegradable, non-renewable and thus leading to high cost of drilling waste treatment. In this work, an environmentally friendly based fluid was developed from a local vegetable oil. Crude palm oil (CPO) was converted to palm methyl ester (PME) via esterification and trans esterification processes. Subsequently, the palm methyl ester was used as a based fluid to formulate oil based muds (OBM) by adjusting the amount of the additives required to achieve the API specifications for mud properties. Full mud check was carried out on eight (8) different PME based mud samples before and after hot rolling at 300°F. PME based mud has comparable properties with conventional synthetic oil based mud. Besides, it passes the acute toxicity test by showing more than 50 survival rates of Poecillia Reticulata marine species upon exposure up to 20000 ppm mud concentration. © 2017 Elsevier B.V.